AMP-independent activator of AMPK for treatment of mitochondrial disorders - Moore, Tereza (PLoS One, 2020)
Mitochondrial diseases are a clinically heterogenous group of disorders caused by respiratory chain dysfunction and associated with progressive, multi-systemic phenotype. There is no effective treatment or cure, and no FDA-approved drug for treating mitochondrial disease. To identify and characterize potential therapeutic compounds, we developed an in vitro screening assay and identified a group of direct AMP-activated protein kinase (AMPK) activators originally developed for the treatment of diabetes and metabolic syndrome. Unlike previously investigated AMPK agonists such as AICAR, these compounds allosterically activate AMPK in an AMP-independent manner, thereby increasing specificity and decreasing pleiotropic effects. The direct AMPK activator PT1 significantly improved mitochondrial function in assays of cellular respiration, energy status, and cellular redox. PT1 also protected against retinal degeneration in a mouse model of photoreceptor degeneration associated with mitochondrial dysfunction and oxidative stress, further supporting the therapeutic potential of AMP-independent AMPK agonists in the treatment of mitochondrial disease.